Utility of Intraoperative Ultrasound in Surgical Management of Lhermitte–Duclos Disease: A Case Report - Parikh, Parth; Nayak, Naren; Goyal, Shubham; Ghosh, Neelanjana; Pandey, Rahul (Asian Journal of Neurosurgery, 2025)
Lhermitte–Duclos disease (LDD) is a rare, autosomal dominant, dysplastic gangliocytoma of the cerebellum. It is a slow-growing benign tumor. The challenges in the surgical resection of these tumors lie in accurately delineating the tumor margin from the normal cerebellar parenchyma. Intraoperative ultrasound has the potential to overcome these limitations. A 30-year-old woman was diagnosed as having LDD showing a typical “tigroid” appearance on MRI. Intraoperative ultrasound was used to delineate the tumor margins and near-total resection was done via right suboccipital craniectomy. The diagnosis was confirmed on histopathological examination. Postoperatively there were no neurological deficits, and the patient is on regular follow-up for screening of Cowden's syndrome. We report this case to highlight the undervalued utility of intraoperative ultrasonography while dealing with patients with LDD. This modality serves as an effective tool to maximize the extent of resection without adding to postoperative morbidity.
Keywords: Lhermitte–Duclos disease; dysplastic gangliocytoma; Cowden's syndrome; intraoperative ultrasound; tigroid appearance